152k views
2 votes
Verify that:

1. (CosX)(CotX) = CscX - SinX

2. (Csc X - CotX)^2 = 1-CosX/1+CosX

These were the last two questions on my Homework that I couldn’t figure out after many tries! Thank you to anyone who helps!

User Ryotsu
by
4.9k points

1 Answer

6 votes

Answer:

See Below.

Explanation:

Problem 1)

We want to verify that:


\displaystyle \left(\cos(x)\right)\left(\cot(x)\right)=\csc(x)-\sin(x)

Note that cot(x) = cos(x) / sin(x). Hence:


\displaystyle \left(\cos(x)\right)\left((\cos(x))/(\sin(x))\right)=\csc(x)-\sin(x)

Multiply:


\displaystyle (\cos^2(x))/(\sin(x))=\csc(x)-\sin(x)

Recall that Pythagorean Identity: sin²(x) + cos²(x) = 1 or cos²(x) = 1 - sin²(x). Substitute:


\displaystyle (1-\sin^2(x))/(\sin(x))=\csc(x)-\sin(x)

Split:


\displaystyle (1)/(\sin(x))-(\sin^2(x))/(\sin(x))=\csc(x)-\sin(x)

Simplify:


\csc(x)-\sin(x)=\csc(x)-\sin(x)

Problem 2)

We want to verify that:


\displaystyle (\csc(x)-\cot(x))^2=(1-\cos(x))/(1+\cos(x))

Square:


\displaystyle \csc^2(x)-2\csc(x)\cot(x)+\cot^2(x)=(1-\cos(x))/(1+\cos(x))

Convert csc(x) to 1 / sin(x) and cot(x) to cos(x) / sin(x). Thus:


\displaystyle (1)/(\sin^2(x))-(2\cos(x))/(\sin^2(x))+(\cos^2(x))/(\sin^2(x))=(1-\cos(x))/(1+\cos(x))

Factor out the sin²(x) from the denominator:


\displaystyle (1)/(\sin^2(x))\left(1-2\cos(x)+\cos^2(x)\right)=(1-\cos(x))/(1+\cos(x))

Factor (perfect square trinomial):


\displaystyle (1)/(\sin^2(x))\left((\cos(x)-1)^2\right)=(1-\cos(x))/(1+\cos(x))

Using the Pythagorean Identity, we know that sin²(x) = 1 - cos²(x). Hence:


\displaystyle ((\cos(x)-1)^2)/(1-\cos^2(x))=(1-\cos(x))/(1+\cos(x))

Factor (difference of two squares):


\displaystyle ((\cos(x)-1)^2)/((1-\cos(x))(1+\cos(x)))=(1-\cos(x))/(1+\cos(x))

Factor out a negative from the first factor in the denominator:


\displaystyle ((\cos(x)-1)^2)/(-(\cos(x)-1)(1+\cos(x)))=(1-\cos(x))/(1+\cos(x))

Cancel:


\displaystyle (\cos(x)-1)/(-(1+\cos(x)))=(1-\cos(x))/(1+\cos(x))

Distribute the negative into the numerator. Therefore:


\displaystyle (1-\cos(x))/(1+\cos(x))=\displaystyle (1-\cos(x))/(1+\cos(x))

User Followben
by
4.7k points